ANALISA KEPUASAN KERJA KARYAWAN YANG DIPENGARUHI WORK LIFE BALANCE, KESELAMATAN DAN KESEHATAN KERJA (K3), BEBAN KERJA PADA PERUSAHAAN GARMENT SKALA RUMAH TANGGA DI KABUPATEN SEMARANG - Kemal Setia Adjie; Yustina Denik Risyanti; Samtono Samtono; Sapto Supriyanto (ITB AAS Indonesia Surakarta, 2024)
The increasingly rapid growth of garment companies on a household scale, such as today, is causing employee dissatisfaction with the work they do. This shows that there are problems that occur, namely the system of alternating employee work holidays, less attention to occupational safety and health for employees, the number of employees is relatively small resulting in the workload received by each employee relatively increasing. This study aims to determine how the balance between work life balance, occupational safety and health and workload influences employee job satisfaction in household-scale clothing companies. This research was conducted quantitatively through surveys, data collection methods using questionnaires processed using the SPSS program, The saturated sample consisted of ninety respondents. The study results show that the work life balance variable has an influence on employee job satisfaction; occupational safety and health variables have an influence on employee job satisfaction; and the workload variable has an influence on employee job satisfaction. Apart from that, the work-life balance variable, occupational safety and health and workload variables simultaneously have an influence on job satisfaction. Keywords: Work Life Balance, Occupational Safety and Health, Workload, Job Satisfaction